Cybercafe physical and electronic security issues (2008)
An overview of physical and electronic security issues in cybercafes in Ibadan city, Nigeria is presented in this chapter. The security measures taken by cybercafe managers for physical and electronic facilities and clients also, were observed in an in-depth study of sixty cybercafes purposively selected for location, popularity, and wide range of services offered, over a period of 2 months. Participatory observation, in-depth interview, and questionnaire methods were adopted, using trained research assistants. Results of the findings showed that cybercafe operators are having a hard time, some folding up due to activities of criminals, and the war against cyber crime can be better tackled if the operators have skilled staff to man the cafes; security measures like passwords that are hard to break, and especially monitor customers who do overnight browsing. Hackers and spammers caught should be handed over to law enforcement agents who will stick to the rule of law.